Environmental, social, and governance communication and actions in Thailand: opportunities and challenges - Pimpa, Nattavud (Frontiers in Communication, 2025)
IntroductionEnvironmental, social, and governance (ESG) factors have become essential considerations for businesses seeking long-term sustainability and stakeholder trust. Effective ESG communication and disclosure practices are critical in demonstrating corporate commitment to sustainability. This study examines how the top 20 companies listed on the Thailand Stock Exchange communicate and disclose ESG-related information, with a focus on their integration of ESG metrics into business strategies.MethodsThis research employs a qualitative approach, utilizing secondary data from sustainability and ESG reports published by the selected companies. Thematic analysis is applied to identify and categorize key ESG activities and disclosure practices, providing a structured assessment of how businesses articulate their ESG commitments.ResultsThe analysis identifies five key themes in ESG communication and disclosure: (1) comprehensive ESG disclosure and reporting, (2) environmental initiatives, (3) employee welfare, (4) governance and risk management, and (5) community development. These themes highlight the diverse approaches taken by companies to integrate ESG factors into their business models and public reporting.DiscussionThe findings underscore the importance of transparent ESG disclosure in enhancing corporate sustainability and stakeholder engagement. Companies that effectively integrate ESG considerations can mitigate risks, identify new business opportunities, and align with global sustainability standards. While the relationship between ESG practices and financial performance remains complex, existing literature suggests that strong ESG commitments can lead to long-term financial benefits. This study provides practical recommendations for Thai businesses to enhance their ESG communication strategies and strengthen their sustainability efforts.